Analisis Laporan Keuangan Kinerja dan Pertumbuhan dalam Industri Perhotelan dengan Metode Analisis Vertikal dan Horizontal pada PT Hotel Sahid Jaya Internasional - Jacklyn Gunadi; Emelien Patricia Ivada; Gisela Olga Kurniawan; Dyah Cahyasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the financial performance of PT Hotel Sahid Jaya International for the period 2020-2023 using vertical and horizontal analysis methods. Vertical analysis evaluates the contribution of each financial statement component to total revenue, while horizontal analysis examines year-over-year growth and performance changes. The findings reveal that, despite significant revenue growth, profitability has consistently declined due to high operational expenses and an increase in the cost of goods sold. Furthermore, the company’s assets have shown a steady decline, marked by a shift in the contribution between current and non-current assets. On the other hand, long-term liabilities have decreased, reflecting better-managed liabilities, while equity remains stable, supported by an increase in retained earnings. Overall, the study highlights critical challenges faced by the company, particularly the shrinking profit margins, underscoring the need for more efficient cost management and operational optimization. Additionally, improving asset and liability management is essential to maintain liquidity and ensure business sustainability. These insights provide valuable guidance for management in formulating strategic decisions to sustain competitiveness and improve financial performance in the hospitality industry. By implementing effective strategies, the company is expected to overcome existing challenges and strengthen its market position. This research contributes not only to understanding the financial dynamics of the company but also offers practical recommendations for long-term growth and resilience in the ever-competitive hospitality sector.